A Look at the Maritime Culture of the Coastal Communities of Muncar Harbor - Anggraeni, Santi; Siregar, Isrina (Swarnadwipa, 2024)
Indonesia is an archipelago that is closely related to maritime activities. Muncar Harbor is one of the maritime centers known as the largest fish producer in East Java. This study aims to examine the maritime culture of the coastal community of Muncar Harbor, which has distinctive characteristics and has been inherited from their ancestors, such as their expertise in catching fish, building boats, and performing rituals to honor the sea that has provided life for them. The author uses various literary studies research techniques, including literature studies, and the stages of historical writing, as well as heuristics, source criticism, interpretation, and historiography in the form of written sources that form the framework of this research. The results show that the culture of the muncar community that has been passed down for generations has experienced acculturation between local culture and Islam. Nevertheless, culture for them is not just a habit but also a way for humans to survive.